Re: The reminder for the execution of a public works project refers to BRACU-NCP/2019/113A - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the execution of a public works project of DESCO for BRACU new campus project.